Building cost comparison between conventional and fully prefabricated systems in Malaysia: a case study of single and double storey house - Haron, Nuzul Azam; Hassim, Salihudin; Abdul Kadir, Mohd Razali (Royal Institution of Surveyors Malaysia, 2007)
In the Malaysia context, the government's policy on housing is that, the traditional building practices must be replaced by Industrialised Building System (IBS), which could save on labour, cost and time of construction and confers quality and durability (Elias, 2000). In so far there is yet no organized body, which can provide information readily on a guideline or benchmark for building cost comparison especially between conventional and fully prefabricated system in Malaysia's construction industry. Hence, the focus of the particular study. A case study was carried out by the researcher. The data required for this case study was generated through interviews. From the results of the case study, it undertaken can be concluded that the conventional construction system is better building cost saving as compared to the fully prefabricated system.